The Influence of Environmental Factors to The Abundance of Scales (Hemiptera: Diaspididae) Population on Apple Crop - Khojin Supriadi; Gatot Mudjiono; Abdul Latief Abadi; Sri Karindah (Journal of Tropical Life Science, 2015)
This research aims to assess the environmental factors that affect the abundance of scales populations on the apple crop. The study was conducted in July 2012 to January 2013. The study was conducted at two sites with different altitude. Bumiaji village's altitude is Â±900 m and Tulungrejo village's altitude is Â±1,515 m asl. Multiple linear regression analysis was conducted to determine the environmental factors that affect the abundance of scales populations on the apple crop. Based on the results of the regression analysis, air temperature and humidity affect the abundance of scales populations in Binangun while rainfall and long solar radiation have no effect. Scales population abundance of the apple crop in Binangun was influenced by air temperature and humidity one week before. Based on the results of the regression analysis, air temperature, air humidity and rainfall affect the abun dance of scales population in Tulungrejo while long solar radiation has no effect. Scales population abundance ofthe apple crop in Tulungrejo was affected by air temperature two weeks before, while humidity and rainfall were affected one week before. The higher air temperature scales, flea population level will increase. And the higherrelative humidity, scales population levels will increase.